1988
DOI: 10.1111/j.1533-8525.1988.tb01259.x
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and Economic Sources of Homicide in the United States

Abstract: Are high rates of homicide better explained by cultural or economic factors? Some research suggests that a regional culture of violence underlies high rates of homicide, whereas other research suggests that poverty or economic inequality increases the likelihood of homicide. A major limitation of this body of research has been the failure of researchers to include an indicator of cultural support for violence that is analytically separate from measures of southern region. In this article, a 12-item Legitimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…However, the state-level demographic variables that we examined-which included temperature, rurality, social composition, and indices of economic and social insecurity-were unable to account for the association between culture of honor and our school-violence indicators, and also were inconsistent predictors of the school-violence variables across the two studies. This marks an important difference between these indicators of school violence and more general indicators of violent crime among adults, which typically show stronger and more consistent associations with temperature, rurality, and environmental-insecurity measures similar to the ones we used (Anderson, 1989;Baron & Straus, 1988;Cohen, 1996;Lee, Bankston, Hayes, & Thomas, 2007). This difference suggests that school violence is a somewhat distinct form of aggression that should not be viewed through standard lenses.…”
Section: Discussionmentioning
confidence: 92%
“…However, the state-level demographic variables that we examined-which included temperature, rurality, social composition, and indices of economic and social insecurity-were unable to account for the association between culture of honor and our school-violence indicators, and also were inconsistent predictors of the school-violence variables across the two studies. This marks an important difference between these indicators of school violence and more general indicators of violent crime among adults, which typically show stronger and more consistent associations with temperature, rurality, and environmental-insecurity measures similar to the ones we used (Anderson, 1989;Baron & Straus, 1988;Cohen, 1996;Lee, Bankston, Hayes, & Thomas, 2007). This difference suggests that school violence is a somewhat distinct form of aggression that should not be viewed through standard lenses.…”
Section: Discussionmentioning
confidence: 92%
“…The macrosystem sources of gender inequality directly affect both aggregate rates of violence and an individual woman's risk of becoming the victim of partner violence (Dobash and Dobash 1979;Smith 1990;Straus 1994;Yllo and Straus 1990). It also influences her risk of suffering health problems, especially those related to sexual health including AIDS (Lawson 1999), of experiencing poverty, unemployment and unhealthy employment conditions (Rice 2001), homicides (Baron and Straus 1988;DeWees and Parker 2003;Titterington 2006;Vieraitis and Williams 2002), rape and sexual violence (Austin and Kim 2000;Yodanis 2004), and more.…”
mentioning
confidence: 97%
“…When transposed into modern settings, the cowboy/gunfighter script or code can even transmit its values to urban minorities (33,34). In the United States, differences between states in consumption of certain gun and crime magazines were found to be partly related to homicide rates and to an overall index of legitimate violence, which included such factors as capital punishment rates, corporal punishment laws, and expenditures by the states on their National Guard military units (35).…”
Section: Social and Environmental Factors Related To Violencementioning
confidence: 99%
“…The unemployable, abandoned, urban youth are the most obvious manifestation of this problem (38). In their study of the United States, Baron and Straus (35) showed that poverty and economic inequality are directly related to both homicide rates and an index of legitimate violence. Another major factor may be the presence of covert economies ("black markets") for such widely demanded products as alcohol, tobacco, marijuana, and cocaine.…”
Section: Social and Environmental Factors Related To Violencementioning
confidence: 99%